The Western crisis of truth in the early 21st century - Grišinas, Arvydas, author. Link
1 online resource (xi, 147 pages)
Keywords: "The Western Crisis of Truth in the Early 21st Century explores the symbolic, experiential, and associative side of contemporary political culture, arguing that phenomena such as 'post-truth', digitalization, mediatization, propaganda, illiberalism or populism, far from being curiosities, have in fact come to represent a uniform aspect of political culture - a challenge to the 'enlightened', 'developed' and 'progressive' world that we believed ourselves to be inhabiting"--